2011
DOI: 10.1057/ap.2011.29
|View full text |Cite
|
Sign up to set email alerts
|

Matching voters to parties: Voting advice applications and models of party choice

Abstract: Online voting advice applications (VAAs) have become very popular and may significantly influence voting behaviour. It is therefore important to ask which model of party choice VAAs follow. We establish that VAAs see party choice largely as proximity-based issue congruence, with some elements of the directional and salience models. We then assess how well VAAs follow the proximity model by comparing policy positions extracted from 13 VAAs in seven European countries with established policy measures from expert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 24 publications
2
41
0
Order By: Relevance
“…Also, the more statements are included on a given dimension, the more voters with a clear position on that dimension get the advice to vote for a party with a similar position on that dimension. This pattern corresponds with findings of Wagner and Ruusuvirta (2012) that increasing the number of statements covering an issue is almost never detrimental. The more politics is 'dimensionalized' for both parties and voters and the more a VAA taps into these dimensions, the more valid the voting advice it produces.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Also, the more statements are included on a given dimension, the more voters with a clear position on that dimension get the advice to vote for a party with a similar position on that dimension. This pattern corresponds with findings of Wagner and Ruusuvirta (2012) that increasing the number of statements covering an issue is almost never detrimental. The more politics is 'dimensionalized' for both parties and voters and the more a VAA taps into these dimensions, the more valid the voting advice it produces.…”
Section: Discussionsupporting
confidence: 89%
“…The plots showed that more statements on the left-right dimension makes VAAs better able to connect voters with parties in a meaningful way (see also Wagner and Ruusuvirta 2012). How many statements are needed is a tricky question, though.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations